Family Role towards Smoking Behaviour among Children in Jakarta - Septiono, Wahyu; Meyrowitsch, Dan Wolf (Kesmas, 2014)
In Indonesia, the prevalence of smoking among 5 – 9 years old children has increased from 0.4% in 2001 to 2% in 2007. Among present adults smokers (>20 years), 17% started to smoke before the age of 13 years. This study identified factors related to smoking behaviour among 8 – 12 years old children in Jakarta, Indonesia using a questionnaire based cross sectional survey to obtain smoking status and possible predictors towards smoking habit. The total sample size was 1,097 students among 3rd - 7th grade students from schools in Jakarta. Self-reported smoking status was defined as whether the child had smoked tobacco within the past two months prior to the interview. The prevalence of smoking was 13.4%. Logistic regression analysis showed that high parental approval on tobacco use (OR=13.4; CI 95%: 5.1 – 35.1) was the strongest predictor on children smoking status, followed by low parental control (OR=12.1; CI 95%: 6.9 – 21.2), being a male compared to a female (OR=10.7; CI 95%: 5.3 – 21.7), mother (OR=10.58; CI 95%: 3.96 – 28.28), father (OR=7.69; CI 95%: 3.59 – 16.47), sibling (OR=7.91; CI 95%: 4.41 – 14.17) smoking status. Smoking parents and siblings, low parental control, and high parental approval on smoking were related to higher odds of smoking among children. The results were used as a rationale for suggestions and recommendations of relevance for future intervention programs and tobacco related research with specific focus on children. Prevalensi anak perokok umur 5-9 tahun di Indonesia meningkat dari 0,4% di tahun 2001 menjadi 2% di tahun 2007. Tujuh belas persen perokok dewasa menyatakan mulai merokok ketika berumur di bawah 13 tahun. Penelitian ini bertujuan untuk menentukan faktor terkait perilaku merokok anak umur 8-12 tahun di Jakarta dengan menggunakan pendekatan potong lintang untuk menjaring perokok anak dan faktor yang mungkin menyebabkan perilaku tersebut. Kuesioner digunakan untuk menjaring status perilaku merokok anak dalam dua bulan terakhir sebelum survei. Total 1.097 murid kelas 3 sampai 7 di Jakarta menjadi sampel penelitian dengan 13,4% responden merokok dalam 2 bulan terakhir. Analisis regresi logistik menunjukkan bahwa pembolehan merokok di dalam rumah oleh orang tua (OR=13,4; CI 95%: 5,1 – 35,1) menjadi penyebab terkuat, diikuti dengan rendahnya kontrol orang tua (OR=12,1; CI 95%: 6,9 – 21,2), siswa laki-laki (OR=10,7; CI 95%: 5,3 – 21,7), ibu (OR=10.58; CI 95%: 3.96 – 28.28), ayah (OR=7,69; CI 95%: 3,59 – 16,47), dan saudara kandung yang perokok (OR=7,91; CI 95%: 4,41 – 14,17). Orang tua dan saudara kandung yang merokok, rendahnya pengawasan orang tua, dan tingginya pembolehan merokok di dalam rumah menjadi penyebab perilaku merokok anak umur 8- 12 tahun. Hasil penelitian dapat dimanfaatkan sebagai rekomendasi untuk program intervensi di masa depan dan penelitian terkait tembakau dengan fokus kepada anak-anak.